REASON WHY XENOPHOBIA REALIZED IN THE SQUID GAME SERIES: A CRITICAL DISCOURSE ANALYSIS - Rizky Femilya Elsa; Rahmad Husein .; Fauziah Khairani Lubis (Universitas Negeri Medan, 2023)
Frequent verbal assaults against immigrants or even physical attacks on outsiders result from intolerance. Experience prejudice and social exclusion due to their foreign backgrounds is inevitable. The study seeks to analyze this portrayal of xenophobia and explore the factors contributing to it. The research conducted explores the origins of xenophobia depicted in Netflix's series, The Squid Game. Utilizing a descriptive qualitative approach, the study delves into the reasons behind the xenophobic attitudes portrayed by the characters. The result showed that due to powerless and statelessness, the immigrants felt the prejudice from the natives. The data, extracted from episodes 1 to 6, focuses on the discrimination faced by immigrant characters within the series. By employing Van Dijk's (2008) theory to analyze the xenophobia, and the analysis integrates aspects of social cognition and context. This framework allows for a comprehensive understanding of the social factors contributing to xenophobia, emphasizing the characters' perspectives and societal context depicted in the show.